An improved heap optimization algorithm for efficient energy management based optimal power flow model. (1st July 2022) - Shaheen, Abdullah M.; El-Sehiemy, Ragab A.; Hasanien, Hany M.; Ginidi, Ahmed R.
Abstract: The optimal power flow is considered as a crucial tool in the power systems' operation and planning. To demonstrate, it aims at minimizing the operational costs of energy production and transmission by adjusting control variables with maintaining economic, operational, and environmental constraints. This article proposes and scrutinizes an Improved Heap-based Optimization Algorithm as a novel technique that successfully enhances the performance of a recently algorithm, namely Heap-based Optimization algorithm to address the optimal power flow problem. In the improved optimizer, an effective exploitation feature is emerged with the conventional version to improve its performance by enhancing the searching around the leader position. This enhancement can avoid being trapped in a local optimum and increase its global search capabilities. For the sake of practicality, the optimizers are developed with diverse objectives of the optimal power flow problem with minimization of fuel cost, emission amount, and transmission power losses with additional restrictions in real power systems that include valve-point effect and security constraints. A proposed multi-objective, improved heap optimization algorithm is investigated to solve multiobjective cases studied. The proposed multi-objective is developed based on the Pareto concept. Three standard systems: IEEE 57-bus system, a large scale 118-bus system, and a practical System are utilized to reveal the suitability and performance of the proposed technique in solving the optimal power flow problem. To illustrate the effectiveness of the proposed optimizer in handling non-convex and diverse scale optimization problems, a comparative analysis has been illustrated with those in the literature. Highlights: An Improved Heap-based Optimization Algorithm addresses the OPF problem. A proposed multi-objective improved heap optimization algorithm is investigated. Three standard systems are utilized to reveal the suitability and performance of the proposed. The effectiveness of the proposed optimizer has been illustrated compared with others. Significant reductions, in the technical economic point of views for single and multiobjective frameworks.